Tracheal intubation using the airtraq for moderately difficult airways: Vstavitev dihalne cevke z uporabo airtraq laringoskopa pri bolnicah z zmerno oteženo vzpostavitvijo dihalne poti - Gerjevič, Božena; Novak–Jankovič, Vesna; Kamenik, Mirt (Acta Medico-Biotechnica, 2021)
Purpose: The Airtraq is a single-use optical laryngoscope designed to facilitate tracheal intubation of normal and difficult airway patients. The purpose of this study was to evaluate the performance of the Airtraq in patients who possessed characteristics associated with an increased risk for difficult intubation. These characteristics were defined based on the following assessments: (1) Mallampati score, (2) thyromental distance, (3) sternomental distance, (4) Cormack and Lehane score.Methods: The present study included 29 patients with an ASA grade 1-2 who were scheduled to undergo gynaecological operations. In each patient, a direct laryngoscopy utilizing the Macintosh laryngoscope was performed prior to intubation with the Airtraq laryngoscope, and several characteristics were evaluated including visibility of the glottis, haemodynamic response, oxygenation, and intubation time.Results: The findings of this study revealed that the Airtraq significantly improved the view of the glottis, as compared with the Macintosh laryngoscope (p=0.02). Likewise, the mean arterial pressure significantly increased (p
Keywords: tracheal intubation; Airtraq; difficult airway; general anaesthesia